Enhancing Work Performance of Extension Agents among Cocoa Farmers in Malaysia: The Influence of Human Resource Development Skills - OLAGUNJU, Oluwatoyin; HASSAN, Salim; SAMAD, Mohd Yusoff Abd; KASIN, Ramle (Walailak Journal of Science and Technology (WJST), 2021)
This study examines the relationships between human resource development skills (leadership, decision making support, and social skills) with the work performance of extension agents among cocoa farmers in Malaysia. The study used stratified sampling technique to select 668 cocoa farmers who were exposed to extension programs facilitated by extension agents of the Malaysian Cocoa Board in 3 regions of Malaysia. The data were analyzed using descriptive statistics, correlation, and regression analyses. The results show that cocoa farmers rated level of work performance, leadership, decision making support, and social skills as high. Significant and positive correlation (p < 0.01) existed between each variable and work performance. Regression analysis results showed that leadership skill, decision making support skill, and social skill were significant predictors to enhance work performance. The R2 value of 0.564 indicates that the 3 skills gave 56.4 % explanation of the variance in extension agents’ work performance. The results also suggested that decision making support skill (β = 0.321) was the most important factor that influenced work performance, followed by leadership skill and social skill. Hence, decision making support skill, leadership skill, and social skill should be taken into consideration in enhancing work performance, especially among farmers and the extension agents who work with them, for continuous performance improvement in their work. The skills that have been identified in this study can be integrated into both the pre-service and in-service training and development of extension agents in their line of work to improve their skills in sharing new technology.